Apiformyia, a new genus of Australian bee flies (Diptera: Bombyliidae, Bombyliinae) with affinities to the New World Heterostylum Macquart - Yeates, David K. (Zootaxa, 2008)
Apiformyia gen. nov. (Diptera: Bombyliidae) is described based on a large series of specimens from the Northern Territory of Australia. The specimens represent a single new species A. australis sp. nov. The genus belongs to the Bombyliinae, and has remarkable anatomical affinities to the New World genus Heterostylum Macquart. In particular, the head of Apiformyia has a sinuous posterior eye margin, but lacks a line bisecting the facets as found in most Anthracinae that also share such an eye margin. A sinuous posterior eye margin is uncommon in the subfamily Bombyliinae, being only found in Heterostylum and four other genera found in the New World, Afrotropical and Palaearctic regions. Additionally, Apiformyia shares with Heterostylum alone an unusual wing venation, with cell R 5 closed, and the apex of cell dm-cu meeting the fork of M 1 and M 2 , there being no stem of M 1+2 . The male genitalia of Apiformyia are generalized bombyliine in form, and do not share the particular unique features of Heterostylum such as the large recurved epiphallus and the gonostylus with apical beak-like process. The female genitalia of Apiformyia lack the sand chamber, acanthophorite spines and presents spermathecae with elongated bulbs, spermathecal ducts more than twice as long as sperm pump and sclerotized collars well developed, also differentiating the genus from Heterostylum.